The Process of Decision-Making in Universities - Lawless, David J (Canadian Journal of Higher Education, 1982)
Canadian universities are considered by some in the public and private sector to be inefficient organizations, largely because of the inability to make decisions related to cost effectiveness. There is a threat to introduce other control mechanisms into the decision-making autonomy of the universities. In fact, universities are very complex organizations and comparable with other complex systems. They are probably as effective in their operation as other organizations in the public and private sector when they are examined according to a set of criteria of effectiveness. They could be compared on these criteria but full data are lacking. In terms of their autonomy Canadian universities enjoy a greater amount of local decision-making than universities in many other countries. British and German universities, although they are quite different, achieve high standards without the same autonomy as Canadian universities. But are they really as efficient and should we allow ourselves to be pushed in the direction of control to which they are subject or should we resist it?